Self‐Assembly of Carboxylic Acid Appended Naphthalene Diimide Derivatives with Tunable Luminescent Color and Electrical Conductivity. Issue 3 (11th December 2013) - Molla, Mijanur Rahaman; Gehrig, Dominik; Roy, Lisa; Kamm, Valentin; Paul, Ankan; Laquai, Frédéric; Ghosh, Suhrit
Abstract Self‐assembly of a series of carboxylic acid‐functionalized naphthalene diimide (NDI) chromophores with a varying number (n=1–4) of methylene spacers between the NDI ring and the carboxylic acid group has been studied. The derivatives show pronounced aggregation due to the synergistic effects of H‐bonding between the carboxylic acid groups in a syn–syn catemer motif and π stacking between the NDI chromophores. Solvent‐dependent UV/Vis studies reveal the existence of monomeric dye molecules in a "good" solvent such as chloroform and self‐assembly in "bad" solvents such as methylcyclohexane. The propensity of self‐assembly is comparable for all samples. Temperature‐dependent spectroscopic studies show high thermal stability of the H‐bonding‐mediated self‐assembled structures. In the presence of a protic solvent such as MeOH, self‐assembly can be suppressed, suggesting a decisive role of H‐bonding, whereas π stacking is more a consequence of than a cause for self‐assembly. Syn–syn catemer‐type H‐bonding is supported by powder XRD studies and the results corroborate well with DFT calculations. The morphology as determined by AFM is found to be dependent on the value of n; with increasing n, the morphology gradually shifts from 2D nanosheets to 1D nanofibers. Emission spectra show sharp emission bands with relatively small Stokes shifts. In addition, a rather broad emission band is observed at longer wavelengths because of the in situ formation of excimer‐type species. Due to such a heterogeneous nature, the emission spectrum spans almost the entire red–green–blue region. Depending on the value of n, the ratio of intensities of the two emission bands is changed, which results in a tunable luminescent color. Furthermore, in the case of n=1 and 3, almost pure white light emission is observed. Time‐resolved photoluminescence spectra show a very short lifetime (a few picoseconds) of monomeric dye molecules and biexponential decays with longer lifetimes (on the order of nanoseconds) for aggregated species. Current–voltage measurements show electrical conductivity in the range of 10−4 S cm−1 for the aggregated chromophores, which is four orders of magnitude higher than the value for a structurally similar NDI control molecule lacking the H‐bonding functionality.